Conservation and divergence in sorgoleone production of sorghum species. Issue 2 (4th March 2020) - Besançon, Thierry E.; Dayan, Franck E.; Gannon, Travis W.; Everman, Wesley J.
Abstract: Sorgoleone‐358 is an important allelochemical of the oily droplets exuded from root hairs of various species in the Sorghum genus. Due to its hydrophobic nature, sorgoleone‐358 can be strongly adsorbed onto soil organic matter, resulting in increased sorgoleone soil persistence. Because of the herbicidal activity of sorgoleone on many small‐seeded weeds, concerns have been raised that sorghum residues may have a detrimental effect on emergence of wheat used as a double crop in the southeastern United States. Laboratory experiments were conducted to evaluate root exudate production and its sorgoleone‐358 content for 36 cultivated sorghum cultivars as well as eight shattercane [ Sorghum bicolor (L.) Moench ssp. arundinaceum (Desv.) de Wet & Harlan] accessions and one johnsongrass [ S. halepense (L.) Pers.] accession. Using a capillary growing mat system, root exudate was extracted with dichloromethane and subjected to chromatography analysis to determine sorgoleone‐358 content. Root biomass of 7‐ to 12‐d‐old seedlings averaged 18.8 mg g −1 seed, and root exudate production ranged from 0.2 and 4.8 mg g −1 root fresh weight (RFW). The amount of sorgoleone produced varied greatly among sorghum accessions. Sorgoleone‐358 amount in the root exudate averaged 0.5 mg g −1 RFW and varied from 0.13 to 1.05 mg g −1 for shattercane cultivar S7 and cultivated sorghum cultivar 992123, respectively. Regarding volume of root biomass, sorgoleone‐358 levels averaged 0.49 mg g −1 (range, 0.06–1.46 mg g −1 ) for sorghum cultivar AAS3479 and shattercane cultivar S2, respectively. Segregation of commercial sorghum cultivars according to their maturity group did not show any difference in root biomass and dry extract production, but early‐maturing cultivars produced on average 18% less sorgoleone‐358 compared with medium‐ and late‐maturing cultivars. These results suggest that sorgoleone production may be genetically constitutive because sorghum growing conditions were identical across cultivars.